Coexistence of Multiple Endocrine Neoplasia Type 2B and Chilaiditi Sign: A Case Report - Deniz Çetin; Mustafa Ünübol; Aykut Soyder; Engin Güney; Adil Coşkun; Serdar Özbaş; Alparslan Ünsal; Muhan Erkuş (Case Reports in Endocrinology)
We present a 15-year-old female patient with medullary thyroid carcinoma, marfanoid habitus, and mucosal ganglioneuromatosis. Our case had a RET protooncogene mutation ser836 polymorphism in exon 14 and ser904 polymorphism in exon 15. Our patient is thought to be atypical MEN2B due to the absence of M918T or A883F mutations. Chilaiditi sign is an incidental radiographic finding of a usually asymptomatic condition in which a part of intestine is located between the liver and diaphragm; however, the term “Chilaiditi syndrome” is used for symptomatic hepatodiaphragmatic interposition. The patient had no symptoms as abdominal pain, constipation, diarrhea, or emesis. Incidentally, Chilaiditi sign was diagnosed with chest radiograph and thoracoabdominal CT. Our case is the first in the literature indicating the coexistence of Chilaiditi sign and MEN2B.